Membangun Time Management Ibu Rumah Tangga yang Baik - Haidilia Maharani; Angga Rovita; Ivan Putranto (Indonesian Journal of Society Engagement, 2022)
Time management is one of the important skills for housewives, it is even one of the keys to success in running a business. Housewives are the first educators in the family. The education provided by parents, especially mothers, is the core and foundation of overall education before taking formal education or living in society. For this reason, a mother figure is needed who can devote her time to her family, and we will see this more often in the figure of a housewife. Being a housewife and taking care of a business will also be very complicated. However, with good time management all these things can be done. Time management is a way that we can do to balance our time for study or work activities, have fun, and rest effectively. We are given the same time by God which is 24 hours. However, there are some people who are successful in dividing their time there are some who are not successful in dividing their time. The main purpose of dividing time is to be able to do things effectively and efficiently. The problem with mothers is that they actually don't like being targeted, but they themselves are targeting themselves. Therefore it needs to be managed efficiently. Effective time management can help do important things in every working hour. In it every individual or leader can use their time well, delegate tasks, organize work, plan the time for meetings (meetings), carry out effective mental and physical rehabilitation after doing heavy work and experiencing heavy pressure. These are some of the main tasks, which can be carried out well. The location of this service is in the cassava chip business, Mrs. Imah Rosyidah, in the Pengsinan Village of Gunung Sindur, Bogor. The purpose of this service is to provide assistance to employees because most of them consist of housewives so that they can manage their time well. The results of this service can be concluded that managing time is very important and needs to be managed properly so that their activities can be organized and do their work optimally.